Community-Acquired Pneumonia Requiring Hospitalization among French Guianese Children - Alexandre Cannesson; Narcisse Elenga (International Journal of Pediatrics)
Community-acquired pneumonia remains a leading cause of hospitalizations among children worldwide. The diagnosis is based on the history, the physical examination results in children with fever plus respiratory signs and symptoms, and chest radiography. The microbiological etiology is confirmed by viral testing and hemocultures. The most likely etiology depends on the age of the child. The features of childhood pneumonia vary between countries and territories. The purpose of this study was to describe the epidemiological characteristics and current microbial ecology of community-acquired pneumonia in children in French Guiana. We performed a retrospective, descriptive, and monocentric study between January 1, 2015, and December 31, 2017, in the pediatric ward of the Cayenne Hospital in French Guiana. The studied population was aged from 0 to 15 years and 3 months and hospitalized for acute community-acquired pneumonia. A total of 415 patients (mean age 3.62 years) were included. A pathogen was identifiable in 22.4% of cases, including bacteria in 61.3%, viruses in 43%, and coinfections in 14%. The main pathogens were respiratory syncytial virus (31.2%), Streptococcus pneumoniae (20.4%), Haemophilus influenzae (11.8%), and Mycoplasma pneumoniae (10.8%). The burden of hospitalization for children with community-acquired pneumonia was highest among less than 2 years, in whom respiratory viruses were the most commonly detected causes of pneumonia. The share of vaccine-preventable diseases (S. pneumoniae, H. influenzae, and influenza) remains high. With the vaccination requirement imposed since 1 January 2018 against pneumococcus, Haemophilus influenzae, and whooping cough and the possibility of practicing multiplex PCR in our hospital, it will be interesting to study the impact of this law enforcement on new child generations and compare these new data to our study.